2005
DOI: 10.1002/adsc.200505040
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence‐Based Assay for Baeyer–Villiger Monooxygenases, Hydroxylases and Lactonases

Abstract: Alkylation of umbelliferone and nitrophenol with chloroacetone, 3-chlorobutanone, 2-chlorocyclopentanone and 2-chlorocyclohexanone gave the corresponding 2-coumaryloxy and 2-nitrophenoxy ketones. The 2-coumaryloxy ketones were used as fluorogenic substrates to detect Baeyer-Villiger monooxygenases activities of microbial cultures in highthroughput using microtiter plates. The 2-coumaryloxy ketones were oxidized by microorganisms producing Baeyer-Villiger monooxygenases (BVMO), releasing umbelliferone as a fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…The substrates can also be prepared in a two -step sequence involving alkylation of umbelliferone with 2 -chloroketones followed by Baeyer -Villiger oxidation. The sequence is particularly interesting for obtaining the fl uorogenic lactones 28 and 29 , which only react with esterases [40] .…”
Section: Fluorogenic Acyloxymethyl Ethersmentioning
confidence: 99%
See 1 more Smart Citation
“…The substrates can also be prepared in a two -step sequence involving alkylation of umbelliferone with 2 -chloroketones followed by Baeyer -Villiger oxidation. The sequence is particularly interesting for obtaining the fl uorogenic lactones 28 and 29 , which only react with esterases [40] .…”
Section: Fluorogenic Acyloxymethyl Ethersmentioning
confidence: 99%
“…It has recently been shown that 2 -aryloxyketones 47 -50 act as fl uorogenic substrates for these enzymes (Scheme 1.15 ) [40] . The natural selectivity of oxidative cleavage leads to insertion of the oxygen atom on the side of the aryl ether to form an unstable lactone or acetal ester, which is rapidly hydrolyzed to form umbelliferone.…”
Section: Baeyer -Villigerasesmentioning
confidence: 99%
“…Generally, percarboxylic acids (i.e., meta-chloroperbenzoic acid (m-CPBA), peracetic acid, etc.) are the most common and suitable oxidants used in BV oxidation, but they are becoming problematic for industrial scale use due to their generating amounts of carboxylic acid waste as side product and resulting in low ester selectivity [7][8][9] . Moreover, percarboxylic acids are expensive, and unstable in solution and typically require chlorinated solvents for improved performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…21, No. 8, 2010 Several methodologies have been applied to screen hydrolases 11 however the fluorogenic substrates coupled to umbelliferone are stable at high temperature and over a broad range of pH-values 12 and have been reported as screening probes for epoxide hydrolases 13 and BaeyerVilliger monooxygenases, 14 using microorganism whole cells. This methodology has been applied to the screening of a great number of activities in strain collections.…”
Section: Introductionmentioning
confidence: 99%
“…This methodology has been applied to the screening of a great number of activities in strain collections. 13,14 The general principle of the method involves a sequence of steps in which a fluorescent probe is released after enzymatic transformation (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%